A new assemblage of late Neanderthal remains from Cova Simanya (NE Iberia) - Morales, Juan I.; Cebrià, Artur; Soto, María; Rodríguez-Hidalgo, Antonio; Hernando, Raquel; Moreno-Ribas, Elena; Lombao, Diego; Rabuñal, José R.; Martín-Perea, David M.; García-Tabernero, Antonio; Allué, Ethel; García-Basanta, Andrea; et al. (Frontiers in Earth Science, 2023)
We present an exceptional collection of 54 late Pleistocene human remains that correspond to at least three Neanderthal individuals from Simanya Gran, the main gallery of Cova Simanya, located in the northeastern Iberian Peninsula. The collection is comprised of 53 unpublished remains unearthed during the 1970s and an additional tooth discovered during 2021 excavations. The specimens represent an adult of small stature, a periadolescent approximately 11.5 years old, and an immature individual aged around 7.7 years, thus offering a more complete demographic perspective. The collection encompasses diverse anatomical parts including upper and lower dentition, mandible, vertebrae, and limb bones from both the upper and lower extremities. Attempts to extract aDNA were unsuccessful. Renewed archaeological investigations at Cova Simanya has facilitated the reevaluation of the original stratigraphic context of these remains, leading to the discovery of the additional tooth, aligning with the periadolescent individual. This assemblage is currently the most extensive Neanderthal collection from the northeastern Mediterranean Iberia, offering invaluable insights into the morphology and evolutionary trajectory of late Pleistocene hominins. As such, Simanya Neanderthals will enhance our understanding of Neanderthal demographics and evolution, paving the way for an in-depth examination of the morphological diversity and evolutionary context of Iberian Neanderthals.